Post-Concussion Syndrome Latent Onset Related to Intracranial Lesion on Head Injury Patient in Dr. M. Djamil General Hospital Padang - Pela Meyadsa; Saiful Saanin; Hesty Lidya Ningsih (HM Publisher, 2022)
Background. Post-concussion syndrome is associated with damaged axons in patients with a mild head injury but little is known about their consequences for brain tissue. This study aims to examine the relationship between latent onset post-concussion and intracranial lesions in head injury patients at Dr. M. Djamil General Hospital Padang. Methods. The research design is an analytical observational study with a cross-sectional approach. A total of 25 patients with head injuries participated in this study with inclusion criteria being hospitalized patients alive without physical and mental disabilities and patients diagnosed with latent onset post-concussion syndrome (PCS) without any additional diagnoses for patients with a history of trauma. Results. The average age of the respondents in this study was 34.08 ± 17.45 years and more than half of the respondents were male, namely 18 (72%) respondents. half of respondents with persistent PCS symptoms > 6 months experienced EDH, as many as 5 (55.6%) respondents, ICH 2 (66.7%) respondents, and cerebral contusion 6 (60%) respondents. The results of statistical tests showed that there was no relationship between latent onset PCS and lesion appearance (p>0.05). The results of statistical tests showed that there was no relationship between latent onset PCS and the degree of head injury (p>0.05). Conclusion. There is no significant relationship between post-concussion syndrome (PCS) latent onset with a degree of head injury and lesion description in head injury patients at Dr. M. Djamil General Hospital Padang.